The Selection of Power Cycle Technology for the Power Generation Island of a Thermonuclear Fusion Power Plant - Donglei WANG; Qi CHEN; Daqian XU; Xiao SUN; Xianyong LUO; Guangtao ZHU (南方能源建设)
[Objective] By adding an energy storage loop, the intermittent energy produced by a thermonuclear fusion reactor can be converted into continuous energy. If this continuous energy is to be further transformed into electricity, which is the most commonly used form of energy for economic and social development, an appropriate power cycle technology must be selected. [Method] Models for both the supercritical carbon dioxide (SCO2) split-flow recompression Brayton cycle and the helium Brayton cycle were established by using Aspen HYSYS software along with the REFPROP physical property calculation method under the China fusion engineering test reactor (CFETR). The effects of main parameters on the cycle efficiency were studied and a comparative analysis of the steam Rankine cycle, the SCO2 split-flow recompression Brayton cycle, and the helium Brayton cycle was conducted. [Method] The SCO2 Brayton cycle is recommended as the power cycle technology for thermonuclear fusion power plants. [Conclusion] The analysis and conclusions regarding the power cycle technology for the power generation island of a thermonuclear fusion power plant can provide important references for subsequent research on fusion power generation technology and engineering design.